Ultrafast metal-insulator-multi-wall carbon nanotube tunneling diode employing asymmetrical structure effect - Shin, J; Im, J; Choi, J; Kim, H; Sohn, J; Cha, S; Jang, J (Elsevier, 2016)
Ultra-fast diode structures based on non-semiconductive materials employing tunneling mechanism have been investigated. Applying the structurally asymmetric effect of multi-wall carbon nanotube (MWCNT) to a vertical metal-insulator-MWCNT (MIC) tunneling diode structure, the ‘on-off’ ratio (∼104) and the current density (38.2 MA/cm2) are drastically enhanced compared to those of conventional metal-insulator-metal (MIM) tunneling diodes. The electrical characteristics are stable up to 423 K. Experimentally, rectifying performance of the MIC diode is good up to 10 MHz and the cut-off frequency of the MIC diode is estimated to be 6.47 THz. The growth process of MWCNT is more controllable for the number and the position than that of SWCNT. Therefore, it has a high probability of realization. The vertically aligned single MWCNT design can guarantee an ultra-high integration density, as well. Therefore, the MIC diode can be applied to various high frequency applications, such as communication devices, high speed electrical switches, and high performance control process units (CPUs), or other new concept devices.